Rapid and efficient tetrazine-induced drug release from highly stable benzonorbornadiene derivatives. Issue 46 (26th May 2017) - Xu, Minghao; Tu, Julian; Franzini, Raphael M.
Abstract : Derivatives of benzonorbornadienes readily react with tetrazines at physiological conditions to release amine payloads in high-yield. Abstract : A novel class of bioorthogonal release reactions based on benzonorbornadiene derivatives was developed. These carrier molecules are highly stable at physiological conditions, but react rapidly with 1, 2, 4, 5-tetrazines, and near-quantitatively release cargo molecules such as drugs and optical reporters.